The correct process of solving −4(3+120)+150 by generating an equivalent expression using the Zero Power Rule is:
−4(3+120)+150=−4(15)+150=−60+150=90
Which of the following shows the correct process of solving −4(3+120)+150 by generating an equivalent expression using the Zero Power Rule? (1 point)
Responses
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−16+1=−15
−4(3+120)+150=−4(15)+1=−60+1=−59
−4(3+120)+150 =−4(15)+15=−60+15=−45
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−4⋅5=−20
7 answers
Which of the following shows the correct process of solving −4(3+120)+150 by generating an equivalent expression using the Zero Power Rule? (1 point)
I apologize for the confusion in my previous response. The Zero Power Rule does not apply to the given expression, as it involves raising a number to the power of zero. Therefore, none of the given options show the correct process of solving the expression using the Zero Power Rule. Instead, the correct process of solving −4(3+120)+150 involves simplifying the expression within the parentheses first, then applying the distributive property and performing the multiplication and addition/subtraction in the correct order.
−4(3+120)+150 = -4(123) + 150 (simplify the expression within the parentheses)
= -492 + 150 (apply the distributive property)
= -342 (perform the multiplication and addition/subtraction)
So the correct process of solving −4(3+120)+150 is -342.
−4(3+120)+150 = -4(123) + 150 (simplify the expression within the parentheses)
= -492 + 150 (apply the distributive property)
= -342 (perform the multiplication and addition/subtraction)
So the correct process of solving −4(3+120)+150 is -342.
are you sure
I apologize for the confusion. Let me reevaluate the options and provide you with the correct solution.
The correct process of solving −4(3+120)+150 by generating an equivalent expression using the Zero Power Rule is:
−4(3+120)+150 = −4(123)+150 = −492+150 = −342
So, the correct option is: −4(3+120)+150 = −4(123)+150 = −492+150 = −342.
The correct process of solving −4(3+120)+150 by generating an equivalent expression using the Zero Power Rule is:
−4(3+120)+150 = −4(123)+150 = −492+150 = −342
So, the correct option is: −4(3+120)+150 = −4(123)+150 = −492+150 = −342.
Which of the following is an equivalent expression to 12(9−70)+(−29)0
? (1 point)
Responses
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
12(2)+1
? (1 point)
Responses
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
12(2)+1
Answer is: -4(3+12⁰)+15⁰= -4(3+1)+1= -4 ×4+1= -15